Arthroscopic-assisted Arthrodesis of the Knee Joint With the Ilizarov Technique: A Case Report and Literature Review. Issue 3 (January 2016) - Waszczykowski, Michal; Niedzielski, Kryspin; Radek, Maciej; Fabis, Jaroslaw
Abstract : Abstract: Arthrodesis of the knee joint is a mainly a salvage surgical procedure performed in cases of infected total knee arthroplasty, tumor, failed knee arthroplasty or posttraumatic complication. The authors report the case of 18-year-old male with posttraumatic complication of left knee because of motorbike accident 1 year before. He was treated immediately after the injury in the local Department of Orthopaedics and Traumatology. The examination in the day of admission to our department revealed deformation of the left knee, massive scar tissue adhesions to the proximal tibial bone and multidirectional instability of the knee. The plain radiographs showed complete lack of lateral compartment of the knee joint and patella. The patient complained of severe instability and pain of the knee and a consecutive loss of supporting function of his left limb. The authors decided to perform an arthroscopic-assisted fusion of the knee with Ilizarov external fixator because of massive scar tissue in the knee region and the prior knee infection. In the final follow-up after 54 months a complete bone fusion, good functional and clinical outcome were obtained. This case provides a significant contribution to the development and application of low-invasive techniques in large and extensive surgical procedures in orthopedics and traumatology. Moreover, in this case fixation of knee joint was crucial for providing good conditions for the regeneration of damaged peroneal nerve.